A study on the relationship between causes of stress and organizational commitment among supporting staff at UiTM Pahang Kampus Jengka / Norhazira A. Karim - A. Karim, Norhazira (Faculty of Business and Management, 2020)
The study was conducted in Universiti Teknologi MARA Cawangan Pahang Kampus Jengka. The purpose of this study was to identify the factors of the relationship between causes of stress and organizational commitment among the supporting staff in UiTM Cawangan Pahang Kampus Jengka. The population taken was all the supporting staff in every department in UiTM Cawangan Pahang Kampus Jengka. The population ofthis study is 224. The researcher decided to take only 140 respondents based on Krejcie and Morgan Theory. The importance of the study is to know the causes of stress that affected employee in the organization. The important of this study were identifying significant causes that influence the organizational commitment among supporting staff in UiTM Cawangan Pahang Kampus Jengka. The observation of causes of stress in UiTM Cawangan Pahang Kampus Jengka shows that the most causes of stress that influence organizational commitment in the organization is harassment.